2022
DOI: 10.1071/an21539
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineralisation status of broilers fed reduced-protein diets supplemented with

Abstract: Context Mineralisation of the bone matrix is a pivotal factor affecting bone strength in broilers. Reduced bone strength might cause fracture during catching and transportation to slaughterhouses, leading to economic loss. Aims This study was conducted to investigate the effects of l-arginine (Arg), guanidinoacetic acid (GAA), and l-citrulline (Cit) supplementation to Arg-deficient reduced-protein diets on bone mineral composition and mineral digestibility of broiler chickens. Methods Day-old Ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Right leg bones including the tibia, femur, and middle toe were separated, cleaned, and dried in a fume hood for 48 h. Then bone weight, length, width, breaking strength, and ash content were measured according to Dao et al. (2022) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Right leg bones including the tibia, femur, and middle toe were separated, cleaned, and dried in a fume hood for 48 h. Then bone weight, length, width, breaking strength, and ash content were measured according to Dao et al. (2022) .…”
Section: Methodsmentioning
confidence: 99%
“…(1998) indicated that tibia weight, length, diameter, radiographic density, and breaking strength were not affected by dietary CP level in broilers. More recently, Dao et al. (2022) reported increased mineral digestibility in broilers fed reduced-protein diets compared to those fed standard protein diets.…”
Section: Introductionmentioning
confidence: 99%
“…Feed samples were also ground using a 0.5 mm screen. Then, mineral levels in feed and excreta were analyzed using an inductively coupled plasma-optical emission spectrometry instrument (Agilent, Mulgrave, VIC, Australia) according to procedures previously described by Dao et al [46]. The apparent mineral digestibility at week 63 was calculated following Dao et al [47].…”
Section: Nutrient Digestibilitymentioning
confidence: 99%
“…The mineral composition in the tibia samples at week 63 was analyzed using an inductively coupled plasma-optical emission spectrometry instrument (Agilent, Mulgrave, VIC, Australia) following procedures previously described by Dao et al [46].…”
Section: Bone Morphology and Mineral Compositionmentioning
confidence: 99%